Mitigation of Temperature Gradients in the Buffer Tank of a Natural Circulation Loop Simulating Passive Decay Heat Removal in a Pool Type Reactor. Issue 15 (7th September 2020) - Spaccapaniccia, Chiara; Planquart, Philippe; Buchlin, Jean-Marie
Abstract: This study considers the decay heat removal through passive systems (i.e., natural convection) in the pool-type experimental reactor MYRRHA (SCKCEN). The low velocities associated with natural convection may cause a degradation of the thermal mixing in the upper plenum of the reactor: buoyancy dominated phenomena, such as stratification, buoyant jets or convective cells may occur. The large temperature gradients associated with these phenomena may induce thermal loads on the structure, compromising its integrity. The objectives of this work are, in order, (1) achieving an understanding of the fluid mechanics leading to the formation of thermal gradients in the upper plenum and (2) mitigating the temperature gradients the upper plenum's geometry. The methodology chosen to address the problem is experimental. A ''two-dimensional'' water facility modeling a slab of the reactor's primary loop was designed. Simultaneous measurements of velocity and temperature were performed in the model's buffer tank using thermocouples and innovative optical imaging techniques. It was observed that vertical thermal gradients develop in the tank because of the combined effect of stratification and advection. Important reductions of local gradients were observed when changing porosity and position of upper plenum's buffer plates.